2007
DOI: 10.1152/ajplung.00481.2006
|View full text |Cite|
|
Sign up to set email alerts
|

Use of consomic rats for genomic insights into ventilator-associated lung injury

Abstract: Use of consomic rats for genomic insights into ventilator-associated lung injury. Am J Physiol Lung Cell Mol Physiol 293: L292-L302, 2007. First published April 27, 2007; doi:10.1152/ajplung.00481.2006.-Increasing evidence supports the contribution of genetic influences on susceptibility/severity in acute lung injury (ALI), a devastating syndrome requiring mechanical ventilation with subsequent risk for ventilatorassociated lung injury (VALI). To identify VALI candidate genes, we determined that Brown Norway (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 53 publications
4
37
0
Order By: Relevance
“…Evan's blue dye (EBD) deposition and BAL protein in lung tissue were used as markers of vascular permeability, as previously described (5,25). The tissue deposition of EBD was measured and normalized to serum EBD for each animal.…”
Section: Histology and Immunohistochemical Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Evan's blue dye (EBD) deposition and BAL protein in lung tissue were used as markers of vascular permeability, as previously described (5,25). The tissue deposition of EBD was measured and normalized to serum EBD for each animal.…”
Section: Histology and Immunohistochemical Stainingmentioning
confidence: 99%
“…We have identified cyclooxygenase-2 (COX-2) as an important candidate gene in ventilator-induced lung injury (5,6). In contrast to COX-1, which is constitutively expressed and involved in housekeeping functions, COX-2 is an inducible enzyme that catalyzes the conversion of arachidonic acid to downstream prostanoids involved in inflammation and vascular homeostasis.…”
mentioning
confidence: 99%
“…Ventilated mice were monitored for blood pressure and arterial blood gas to ensure adequate perfusion. Bronchoalveolar lavage (BAL) fluid was collected and indices of lung vascular leak were assessed as previously described (14). All animal experiments were approved by the Animal Care and Use Committees of the University of Illinois at Chicago, Chicago, IL.…”
Section: Preclinical Model Of Vilimentioning
confidence: 99%
“…Expression profiling was performed using Affymetrix Mouse 430 2.0 arrays and protocols (Affymetrix, Santa Clara, CA) as described previously (14). Chips were scanned using a GeneChip Scanner 3000 (Affymetrix).…”
Section: Treatment Of Gadd45amentioning
confidence: 99%
“…84 For example, introgressions of VALI-sensitive BN chromosomes 13 and 16 into the VALIresistant SS resulted in significantly increased inflammation (compared with parental SS strain), which suggests that genes residing on BN chromosomes 13 and 16 confer increased sensitivity to high tidal volume ventilation. Interestingly, previous animal studies have identified several VALI/ALI candidate genes (IL-6, PAI1, CCL2, COX2) that map to these chromosomes, which increases their potential role in the VALI phenotype.…”
Section: Novel Animal Models: Consomic and Congenic Rodentsmentioning
confidence: 99%